THE ORIGINS OF THE KHARKІV SCHOOL OF POLITICAL ANALYSIS AND ITS INFLUENCE ON THE FORMATION OF THE THEORY AND METHODOLOGY OF POLITICAL ANALYTICS - Рубанов, В. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
Based on critical reviews of scholarly works as well as theoretical and applied projects of the Kharkiv University professors, the article constitutes one of the first attempts at academic estimation of Ukrainian school of political analysis and its development back in the 19th century. The author maintains that the school, as far as academic research of politics concerns, was not inferior to the highest contemporary European standards, and was successfully developing on the national level through the efforts of scholars of Kharkiv. Thus it had clear positive impact on the global process of framing up the theory and methodology of political analytics in general.